Desenvolvimento e testes de software de um receptor de GPS para uso espacial - Raposo, Tullio Emmanuel Messias (2011)
Spacecraft move with high speeds and suffer abrupt changes in acceleration. So, an onboard GPS receiver could calculate navigation solutions if the Doppler effect is taken into consideration during the satellite signals acquisition and tracking. Thus, for the receiver subject to such dynamic cope these shifts in the frequency signal, resulting from this effect, it is imperative to adjust its acquisition bandwidth and increase its tracking loop to a higher order. This paper presents the changes in the GPS Orion s software, an open architecture receiver produced by GEC Plessey Semiconductors, nowadays Zarlink, in order to make it able to generate navigation fix for vehicle under high dynamics, especially Low Earth Orbit satellites. GPS Architect development system, sold by the same company, supported the modifications. Furthermore, it presents GPS Monitor Aerospace s characteristics, a computational tool developed for monitoring navigation fix calculated by the GPS receiver, through graphics. Although it was not possible to simulate the software modifications implemented in the receiver in high dynamics, it was observed that the receiver worked in stationary tests, verified also in the new interface. This work also presents the results of GPS Receiver for Aerospace Applications experiment, achieved with the receiver s participation in a suborbital mission, Operation Maracati 2, in December 2010, using a digital second order carrier tracking loop. Despite an incident moments before the launch have hindered the effective navigation of the receiver, it was observed that the experiment worked properly, acquiring new satellites and tracking them during the VSB-30 rocket flight.